Peculiarities of international labour migration from China to Russia (on the example of the far East federal district) - Mishchuk, S. N. (Ekonomika regiona, 2014)
In the paper, the dynamics of contemporary international migration, which strength the role of the Asia-Pacific region’s (including China) are shown. The author assessed the current status and possible scenarios of migration flows from China to Russia. On the example of the Jewish Autonomous Region, it is shown that the fluctuating scenario is to be accepted as the most possible. In the article, the dynamics of international labor migration in the southern Russian Far East subjects due to the distinct character of the cross-border position the Russian Far East and North-Eastern provinces of China are analyzed in depth. The author assessed the perception of international migration by the population of southern Russian Far East subjects on the content base analysis. It is emphasized that the continued involvement of labor immigrants has led to a decrease in the professional level of the population of the Russian regions, which is reflected at the background of the declining interest of Chinese migrants to work in the territory of Russia.